Industrial training report: Wisma Felda Global Venture (FGV) / Muhammad Aiman Nik Faizal - Nik Faizal, Muhammad Aiman (Universiti Teknologi MARA, Perlis, 2024)
My six-month industrial training programmed started here at Wisma Felda Global Venture (FGV) and it was memorable and interesting. The information in this internship report relates to the time. I spent interning at Wisma Felda Global Venture (FGV) Human Resource Department, which lasted from 04 September 2023 until 09 February 2024. I have been assigned to work in the human resource department under the supervision of Puan Norhayati Bt Hamdan. Here, I had learn many things that new such as on how fill the Talent Individual Development Plan, create invitation letter for employee (surat panggilan kursus), joining interview new candidate, fill in grant application for employee's training (HRDCorp), Fill in Employee Requisition Form (ERF) and many more. I succeed in every task that given to me by my manager other staff. On the other hand, the strength of this report is the part of SWOT analysis.The SWOT analysis section, the primary results of this study are focused on a variety of crucial factors, including strengths, weaknesses, opportunities, and threats. In this report I have been focusing the SWOT analysis for the human resources department.